Narratives of Violence: The White ImagiNation, and the Making of Black Masculinity in ‘City of God’ - Jaime Amparo Alves (Revista CS)
The article explores the representation of young-black men in the 2002 film City of God. The film deploys “pathological scripts” of Black masculinity in Brazil as criminal and deviant. The controlling image of Black men’s bodies as a source of danger and impurity sustains Brazilian regime of racial domination, and the narratives of violence make explicit the ways in which the Brazilian nation is imagined though a racial underpinning. Blackness is consumed as an exotic commodity, yet is also understood as a threat to national harmony. The nation is, then, written and re-imagined as a racial paradise, but mostly by inscribing death on the black body.